ANALISIS FAKTOR KEPATUHAN PENGGUNAAN OBAT ANTI DIABETES PADA PENDERITA DIABETES MELLITUS DI KLINIK AMPEL SEHAT WIROLEGI JEMBER - Marwah; Emi Eliya Astutik (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2018)
In DM which is a chronic disease and requires long-term therapy, the use of OAD should not be interrupted to maintain the stability of glucose levels in the blood and prevent complications. Family support is very influential on increasing patient self-esteem because with family support, patients will feel cared for, loved, valued by the family, more sincere and positive in accepting disease conditions that affect their self-esteem so that healing and treatment will be better. The purpose of this study was to analyze factors related to compliance with the use of anti-diabetes drugs in people with diabetes mellitus in the Ampel Sehat Clinic, Wirolegi Jember. The research design used in this study is analytic correlation using a cross-sectional approach. The population in this study were all patients with diabetes mellitus who treated 70 people. The sample in this study were 41 people with Non Probability sampling or accidental sampling technique. Measuring instrument used by the questionnaire. The results of data analysis, the level of knowledge about the use of anti-diabetes mellitus drugs most of the categories either by 23 or 56.10%, medium categories and less as much as 18 or 42.90%. Respondents' family support for the use of anti-diabetic drugs in good category is 20 people or 48.8%. Respondents' level of adherence to the use of anti-diabetes drugs was 22 or 53.7%, followed by 12 or 29.30% less adherents and 7 or 17.00% non-adherents. Statistical test results with the Sparman test obtained p value 0,000 or <α (0.05). This proves that Ho was rejected and Ha was accepted and it can be concluded that there is a relationship between knowledge and family support for the compliance of drug use in patients with diabetes mellitus in the Ampel Sehat Clinic, Wirolegi Jember 2016. It is recommended that DM sufferers comply with the use of drugs.